The Relevance of 'EFL', 'ESL' and Other Such Terms in Contemporary Contexts: The Case of Malaysian English - Azirah Hashim; Gerhard Leitner (Cranmore Publishing, 2021)
English in Malaysia has undergone several phases since it entered the country during the colonial period in the early nineteenth century. During the colonial period, English was used mainly for communicating between the colonialists and traders. English was the official language together with Malay when the country attained independence in 1957. However, it lost its status as an official language after ten years, in 1967, when Malay was made the sole official language. The medium of instruction which had been English gradually changed to Malay during the 1970s and 1980s with a deliberate reduction of the role of English in schools. In later years, nevertheless, there was official promotion of English arising from Malay being already firmly established as the national language and the need to keep abreast with global and regional changes. The status of English has, thus, shifted several times throughout the country's post-colonial period. While it became the "second most important language" nationally and politically, there emerged some variation in its status in some domains, in speech vs writing and, of course, among individuals. Dynamic changes in Malaysian English have also taken place. This paper examines the developments in terms of the status of English in Malaysia, including terms like 'EFL' and 'ESL' which have been used, and discusses if they are still adequate. We will show how the status of English and the contexts of its uses have changed and why a single term, say 'second language', is of little use and has been throughout its history. We will conclude with tentative propositions of what might happen in the future.